Assessment of role of FPIs in MCH-FP programme in Bangladesh - Ahmad, S. (Shamsuddin), 1950- (National Institute of Population Research and Training], 1994)
On role of Family Planning Inspectors in Maternal and Child Health-Family Planning Programme.